Associations between Psychosocial Working Conditions and Work-Specific Self-Efficacy Beliefs Among Employees Receiving Psychotherapeutic Consultation at Work - Weber, Jeannette; Hansmann, Marieke; Heming, Meike; Herold, Regina; Erim, Yesim; Hander, Nicole; Rothermund, Eva; Mulfinger, Nadine; Kröger, Christoph; Feißt, Manuel; Brezinski, Jolanda; Kohl, Fiona; et al. (Journal of Occupational Rehabilitation, 2024)
Purpose: By considering work-related aspects during early intervention and treatment of employees with (subclinical) symptoms of common mental disorders, psychotherapeutic consultation at work (PT-W) aims to increase work-specific self-efficacy (SE) to finally reduce sickness absence and contribute to successful return to work. This study, thus, aims to investigate interrelations between working conditions and work-specific SE among employees before receiving PT-W. Methods: The study uses baseline data of a randomized controlled trial testing the efficacy of PT-W in Germany (n = 535). Working conditions were assessed by six scales of the validated Copenhagen Psychosocial Questionnaire (COPSOQ). SE was assessed by the validated general short occupational self-efficacy (OSE) scale and return-to-work self-efficacy (RTW-SE) scale, two specific forms of self-efficacy. Multiple linear regression models were calculated using working conditions as independent and self-efficacy as dependent variables. Interactions between working conditions and age, gender and current extent of work were added to those models. Results: Results suggest that quantitative job demands are negatively and development opportunities are positively related to OSE and RTW-SE. Age did not moderate those relationships. The association between development opportunities and OSE was stronger among employees indicating working less number of hours than specified in their contract compared to employees indicating working their full contract hours. Furthermore, interactions with gender were found with social support being only (positively) associated with OSE among male and decision authority being only (positively) associated with OSE among female employees. Conclusions: The associations between working conditions and work-specific SE support the usefulness of addressing potential reciprocal relationships between those two variables during PT-W to improve mental health of employees. Trial registration number: Registered at the German Clinical Trial Register (DRKS) at 01.03.2021—DRKS00023049.
CRIS-Team Scopus Importer:2024-12-13
Keywords: Mental health; Occupational health; Occupational stress; Psychotherapeutic care; Self-efficacy; Workplace